Attitude toward physical activity: an investigation of sports science students in Malaysian public universities / Kee Kang Mea and Wee Eng Hoe - Wee, Eng Hoe; Kee, Kang Mea (Pusat Penerbitan Universiti (UPENA), 2005)
The purpose of this study was to investigate the attitude of sports science undergraduates toward physical activity and the six perceived meaning of physical activity. The study employed the Kenyon ATPA instrument to determine the attitude toward physical activity of the respondents. A total of 639 sports science and physical education undergraduates from the six public universities completed the questionnaires. The findings of this study showed that there were significant differences in the overall attitude and the six perceived meaning toward physical activity of Malaysian public universities sports science students based on gender except for the Aesthetic and the Catharsis sub-domains. However, there was no significant difference in their overall attitude toward physical activity by their age and ethnic groups. In conclusion, the sports science or physical education major students differ in term of their overall attitude toward physical activity and perceived meaning of physical activity based on gender. Females are more inclined to participate in physical activity for health and fitness purposes besides for socialization experience whereas the males are more likely to participate in physical activity as a way to release tension and aggression besides for socialisation. Hence gender is an important factor in determining the type of physical activity programs to organise for college students. The results of this study also indicate that enrolling in sport science courses may help to generate positive impact on attitude toward physical activity.